The Strategy of Sosial Media Marketing in Influencing Consumer Financial Behavior: A Tiktok Case Study - Amien, Neneng Nurbaeti; Reina A. Hadikusumo; Yimmi Syavardie (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the impact of TikTok-based social media marketing strategies on consumer financial behavior, focusing on spending, saving, and investment decisions. Utilizing a qualitative approach, the research gathered data through library research and literature review methods, analyzing sources such as academic journals, books, and reputable online platforms. The findings reveal that TikTok marketing tactics, including influencer endorsements, viral challenges, and educational content, have a notable influence on consumer financial behavior. These strategies effectively leverage emotional appeal, peer influence, and algorithmic content delivery, fostering impulsive spending, enhancing brand loyalty, and promoting financial literacy. Additionally, the role of micro-influencers and user-generated content significantly shapes consumer actions and perceptions. The study concludes that TikTok offers an effective platform for businesses to engage consumers and influence financial decisions, though it also highlights the need for careful management of ethical concerns and the risk of misinformation.